A walking life : reclaiming our health and our freedom one step at a time - Malchik, Antonia (Da Capo Lifelong Books, 2019)
"An incisive, utterly engaging exploration of walking: how it is fundamental to our being human, how we've designed it out of our lives, and how it is essential that we reembrace it." --Amazon.com.